Validation of the Emotion Regulation Questionnaire (ERQ): Network Analysis as an Alternative of Confirmatory Factor Analysis (CFA) - Christiany Suwartono; Dewa Bintamur (ANIMA Indonesian Psychological Journal, 2019)
Construct validity with a confirmatory factor analysis (CFA) method is often used by researchers to identify the structure of psychological measurement. Although this CFA method has provided a complete evaluation of the structure of the test, sometimes there is no consensus reached regarding the number of factors. With the CFA method, researchers determined and compared several models to choose the adequate scale structure, including the number of factors in a scale. The network analysis can play a role to help researchers. In this network analysis, the results of the analysis presented in a visual form, which can facilitate the researchers quickly identify the scale structure based on the relations, displayed in the form of lines (thick-thin) and colors (green-red). Current research aims to test the reliability and construct validity; also, shows that network analysis can be an alternative in presenting visualizations and interpretations compare with factor analysis methods, especially CFA. We used The Emotion Regulation Questionnaire (ERQ) with 954 participants aged 16-57 years. The results are either, with the CFA analysis method or network analysis; it is evident that ERQ has two factors, namely suppression and reappraisal. The results show that the network analysis method can be used as an alternative in identifying the structure of the psychological scale.